1991
DOI: 10.1088/0953-8984/3/47/006
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-produced electron and hole centres in oxygen-containing BaFBr. I. EPR and ODEPR studies

Abstract: An 0centre formed upon hole trapping by 0'in X-irradiated BaFBr is long-lived at room temperature and has been detected by EPR below 30 K. It can also be produced in low wncentrations by expos-of BaFBr to subbandgap (200400 nm) radiation. The formation of F(Br-) centres at chargecompensating bromide ion vacancies is a corollary of the photoionivltion of Oz-. High eoneentrations of oxide have been successfully introduced into this material by doping with anhydrous BaO. including Ba"O for unambiguous identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Both the formation of BaO through the decomposition of BaCO 3 and the formation of oxygen through the CO 2 reduction are hold responsible for oxygen incorporation into the BaFBr:Eu 2þ lattice and the generation of bromine based anion vacancies (F þ (Br)-centers). EPR confirms this line of thinking and has shown that O 2À can occupy different halide sites in BaFBr:Eu 2þ but favorably replaces fluoride ions thereby acting as charge compensation centers for F þ (Br)-centers as anion vacancies (Eachus et al, 1991). Most likely the excess of fluoride ions following from Eq.…”
Section: Synthesis Of the Storage Phosphorsupporting
confidence: 53%
“…Both the formation of BaO through the decomposition of BaCO 3 and the formation of oxygen through the CO 2 reduction are hold responsible for oxygen incorporation into the BaFBr:Eu 2þ lattice and the generation of bromine based anion vacancies (F þ (Br)-centers). EPR confirms this line of thinking and has shown that O 2À can occupy different halide sites in BaFBr:Eu 2þ but favorably replaces fluoride ions thereby acting as charge compensation centers for F þ (Br)-centers as anion vacancies (Eachus et al, 1991). Most likely the excess of fluoride ions following from Eq.…”
Section: Synthesis Of the Storage Phosphorsupporting
confidence: 53%
“…After the exciton decay the electron is trapped at that vacancy and the V K center formed migrates away at room temperature and may transfer its hole to another defect ͑note, V K centers are not stable at room temperature 9,15-17 ͒. For example, it reacts with O F 2Ϫ to form O F Ϫ , 15,16 but there may also be another, unknown, hole center ͑see the discussion in Ref. 3-5͒. It seems that for the preferential generation of F͑Br Ϫ ͒ and F A ͑Br Ϫ ͒ centers the origin of the Br Ϫ vacancies is not important.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of experimental support for the described models gave rise to a third proposal for the formation of defect centers by Spaeth et al [16,17,18,19,20]. This model equally assumes that vacancies are already present in the virgin lattice.…”
Section: Bafbr:eu2+ Psl Mechanismmentioning
confidence: 99%